Materials and Chemistry of Flame-Retardant Polyurethanes. Green Flame Retardants - Gupta, Ram K., editor 645596; ACS Publications (Online service) 645714 (Washington, DC : American Chemical Society, 2021)
Developing Green and Sustainable Materials. Polyurethane is one of the fastest-growing industries with a wide variety of commercial applications. Unfortunately, the high flammability of polyurethane foams restricts valuable developments. This two-volume (1399, 1400) set presents the state of the field of flame-retardant polyurethanes. This volume focuses green and sustainable materials, with a focus on specific materials and mechanisms for future development of new materials. This comprehensive set will be a valuable tool for scientists and researchers working on polyurethanes in both academia and industry.